The Role of Educational Psychologists in Fuelling the Narrative of the “Velcro TA” - Vivash, Joanna; Morgan, Gavin (Frontiers in Education, 2019)
The notion of ‘Statementing’ borne out of the recommendations of the Warnock Report (1978) set in motion unprecedented reforms in the use and allocation of resources, including the use of Teaching Assistants (TAs), in supporting children with Special Educational Needs and Disabilities (SEND). There has been a move however to question the efficacy of TAs, which has led to a number of studies into their effectiveness. Concern remains around the idea of what has colloquially become known as the ‘Velcro TA’, and how support can provide scaffolded and independent learning. Central to the assessment process of Statements of Special Educational Needs, and current Education Health and Care Plans (EHCP), educational psychologists (EPs) have a prominent role to play in providing advice around provision and the effective use of resources. Consideration therefore needs to be made as to how EPs may contribute to the construct of the ‘Velcro TA’. This paper explores the role of EPs in contributing to this through a consideration of how EPs discuss support through written psychological advice for Statements of SEN/EHCPs and by exploring the perspectives of school staff of how support is delivered in practice. The historical Psychological Advice of ten pupils were analysed using Thematic Analysis. Of these ten pupils, interviews with members of current school staff for five of the pupils were transcribed and the data analysed using Thematic Analysis. These interviews included five SENCOs, five Teachers and five TAs. The results from the Thematic Analysis of the psychological advice identified that EP advice does not seem to have contributed to a notion of a Velcro TA and the theme of Independence was prominent throughout. However, analysis from both the psychological advice and the school staff interviews identified an overarching theme of Ambiguity which underpinned many of the themes, including themes of Classroom Practice and Role of Others. The analysis from the psychological advice identified that there was often a sense of ‘what to do’ but not necessarily ‘how to do it’ and it appears that this Ambiguity is reflected into school staff practice.